Implementation of Collaborative Learning Model to Improve Student Literacy at Muhammadiyah Elementary School in Bima City - Musfirah; Ades S. Anhar; Ahmadin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to determine the effectiveness of the implementation of the Collaborative Learning Model starting from the need to create a more interactive learning environment based on cooperation between students. Traditional learning that is more passive, where the teacher is the main source of information, is considered less effective in developing students' social skills, critical thinking, and problem solving abilities. Education is the key to an individual's success. Therefore, we as educators must be able to develop ourselves as whole individuals, as members of society and citizens of the nation. In other words, being able to know ourselves, the surrounding community, and our nation. This introduction process requires the development of cognitive, affective abilities, including imagination and inspiration (Hamid Hasan, 1993: 128). The results of this study indicate that the implementation of the collaborative learning model can significantly increase student literacy, collaborative students have higher literacy, collaboration needs to be applied among students and students in schools. These collaborative learning methods further motivate or encourage students to be active and interactive and work together in completing academic tasks in class. Thus, collaborative learning is fundamentally different from the conventional-traditional approach that has been carried out so far, which is more direct-transfer or one-way transmission model. The conclusion is that learning model research can be used as an alternative to improve literacy. In this case, students become the only source of knowledge or skills. Collaborative learning views the learning process more as learner-centered and not teacher-centered.